The linkages between growth, poverty and inequality in Vietnam: An empirical analysis - Hoai Nam Nguyen (Accounting, 2020)
This paper examines how initial inequality and poverty rate are related to subsequent economic growth in the provincial level of Vietnam. The results show a robust negative relationship between initial poverty rate and subsequent economic growth. However, there is no link between initial inequality and subsequent economic growth. The results also show that lower inequality leads to lower poverty rate and poverty reduction could help to reduce inequality. Other determinants of inequality and poverty reduction include human capital, investment, gross domestic product (GDP) growth rate and trade openness. The main policy implication that emerges from this paper is that concentrating on poverty elimination will help us build a more equitable society without sacrificing economic growth.